UPAYA MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN HURUF AWAS BAGI ANAK LOW VISION MELALUI MODIFIKASI HURUF - Ismidar - Rahman (Jurnal Penelitian Pendidikan Khusus, 2013)
The background research is still usually low vision children class I in special schools Fan redha Padang to write letters beginning alert especially on vowels a, i, u, e, o. The ability to write such, hold a pencil can as well but the shape of the letter made clear the child and the child is not often scribbled with lines that are not clear. This is because the child’s vision is not the same as any other normal child’s vision. This study bertujauan to improve writing skills beginning alert the vowel letters a, i, u, e, o the Children's Low Vision X class I through modification letter. Type of research is the SSR (Single Subject Research) in one subject of study that Children Low Vision X Class I in SLB Fan Redha Padang using ABA design n data were analyzed using visual data analysis are illustrated by a graph. Analysis of the data shows an increase in the ability to write letters to the Children's Low Vision through modification of the letter where the letters are enlarged and the bold. It is seen from the results of the analysis showed that the amount of data overlape percentage of 0% for the comparison with the baseline condition I Intervention condition. As for the comparison of the condition of Intervention and Baseline II shows the percentage of data overlape at 0%. This proves that the impact of the provision of intervention (through the modification of the letter) to changes in the target behavior, ie, an increase writing skill in children with low vision. Based on data analysis that has been done, it can be concluded that with modifications to improve the ability to write letters beginning for children with Low Vision in special schools Fan Redha Padang.